(untitled) (Research, Society and Development, 2021)
Among the mental disorders that are growing the most today, it can be mentioned and conceptualized that Panic Disorder (PD) is an anxiety disorder known for its negative impact on patients’ quality of life (QOL), regardless of other factors. Based on the above, the objective is to discuss, in the light of evidence, how Psychoanalysis can be used for the Treatment of Panic Disorder, as well as to identify which are the triggers responsible for developing the mental disorder in question, and how health professionals they can work helping to reduce and remit clinical cases associated with PD. The exact causes of panic syndrome are unknown, although Science believes that a set of factors can trigger the development of this disorder: extreme stress situations; financial crises; fights; separations or deaths in the family; traumatic experiences in childhood or after robberies and kidnappings; A bibliographic study was conducted using electronic databases Scielo and VHL, using the descriptors registered in Health Science-DeCS: Psychoanalysis, Panic Disorder, Causes and Health Professionals. Consisting of a selective and interpretive observation of the same, extracting relevant points, in order to give this research an explanatory condition. Thus, it is concluded that it is necessary to train health professionals to approach people with PD. In addition, measures should be applied to the population on how to recognize what triggers their crises (which are the triggers), in addition to increasing the presence of both hospital and clinical psychologists through the NASF in the FHS, promoting biopsychosocial care.